The relative contribution of metabolic and structural abnormalities to diastolic dysfunction in obesity - Rayner, J J; Banerjee, R; Holloway, C J; Lewis, A J M; Peterzan, M A; Francis, J M; Neubauer, S; Rider, O J (International Journal of Obesity, 2018)
Background: Obesity causes diastolic dysfunction, and is one of the leading causes of heart failure with preserved ejection fraction. Myocardial relaxation is determined by both active metabolic processes such as impaired energetic status and steatosis, as well as intrinsic myocardial remodelling. However, the relative contribution of each to diastolic dysfunction in obesity is currently unknown. Methods: Eighty adult subjects (48 male) with no cardiovascular risk factors across a wide range of body mass indices (18.4–53.0 kg m −2 ) underwent magnetic resonance imaging for abdominal visceral fat, left ventricular geometry (LV mass:volume ratio) and diastolic function (peak diastolic strain rate), and magnetic resonance spectroscopy for PCr/ATP and myocardial triglyceride content. Results: Increasing visceral obesity was related to diastolic dysfunction (peak diastolic strain rate, r =−0.46, P =0.001). Myocardial triglyceride content (β=−0.2, P =0.008), PCr/ATP (β=−0.22, P =0.04) and LV mass:volume ratio (β=−0.61, P =0.04) all independently predicted peak diastolic strain rate (model R 2 0.36, P <0.001). Moderated multiple regression confirmed the full mediating roles of PCr/ATP, myocardial triglyceride content and LV mass:volume ratio in the relationship between visceral fat and peak diastolic strain rate. Of the negative effect of visceral fat on diastolic function, 40% was explained by increased myocardial triglycerides, 39% by reduced PCr/ATP and 21% by LV concentric remodelling. Conclusions: Myocardial energetics and steatosis are more important in determining LV diastolic function than concentric hypertrophy, accounting for more of the negative effect of obesity on diastolic function than LV geometric remodelling. Targeting these metabolic processes is an attractive strategy to treat diastolic dysfunction in obesity.